What comes before phonics? - Neaum, Sally (Thousand Oaks, California Sage, 2017)
"This book looks in detail at the knowledge, understanding, skills and attitudes that children need to enable them to come to phonics teaching ready to learn and with a good chance of success. It explores a range of aspects of young children's learning that lead into literacy, and includes practical advice on how to translate this into practice"--Back cover.
1. Early literacy: the current context -- 2. Leading into literacy -- 3. Speaking and listening -- 4. Physical foundations of literacy -- Metalinguistic development -- 6. Print awareness -- 7. Symbolising and representation -- 8. Phonological awareness.
Keywords: Reading -- Phonetic method; Language arts (Early childhood)